Profile of quinoa consumption and consumers’ perception of its nutritional and functional value (Research, Society and Development, 2022)
Quinoa is a grain from the Andean region in South America that possesses high potential due to its nutritional and functional qualities. However, outside the Andean region, quinoa is rarely consumed. This may happen due to lack of knowledge about their nutritional quality and health benefits or the high cost of importing the grains. Taking that into account, the study aimed to evaluate the profile of Brazilian consumers in relation to the use of quinoa in food, knowledge about its nutritional value and health benefits of its consumption. Data were obtained through an online form and analyzed using Epi Info® software. The survey was carried out with 406 people and showed that the profile was predominantly female who were 36 to 50 years old. Most of the interviewed public have omnivorous food. It was found that the 258 respondents knew about quinoa and 187 said they consume or have already consumed the grains. The frequency of consumption is sporadic with white quinoa being the most used one. Knowledge about quinoa and its health benefits is little which can influence the frequency and interest in its consumption. Thus, it is extremely important that works are published regarding quinoa and its nutritional value and health benefits in order to encourage its introduction into population’s diet as well as to stimulate food industries make use of it as an ingredient in the production of nutritious and functional food.